2017
DOI: 10.1017/s0016756817000735
|View full text |Cite
|
Sign up to set email alerts
|

Late Triassic ecosystem variations inferred by palynological records from Hechuan, southern Sichuan Basin, China

Abstract: -The Late Triassic deposits of the Sichuan Basin, southwestern China are significant for hosting abundant and diverse fossil assemblages including plants (containing spores and pollen), bivalves and insects. However, the Late Triassic palaeoecological variations are still poorly documented in this region. Here we present results from a palynological study from the Upper Triassic Xujiahe Formation in Hechuan of Chongqing, southern Sichuan Basin. The palynological analysis revealed a well-preserved terrestrial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…A cooler and drier condition in the latest Triassic has also been revealed by palynological data from Hechuan region in the southern Sichuan Basin (Li et al, 2018). Recent sedimentary and biomarker studies suggested increased wildfire activity during the Triassic-Jurassic transition within the Sichuan Basin (Pole et al, 2018;Song et al, 2020), possibly as a result of the warmer and drier climate during this interval.…”
Section: Climate Changes Across the Triassic-jurassic Transitionmentioning
confidence: 74%
See 3 more Smart Citations
“…A cooler and drier condition in the latest Triassic has also been revealed by palynological data from Hechuan region in the southern Sichuan Basin (Li et al, 2018). Recent sedimentary and biomarker studies suggested increased wildfire activity during the Triassic-Jurassic transition within the Sichuan Basin (Pole et al, 2018;Song et al, 2020), possibly as a result of the warmer and drier climate during this interval.…”
Section: Climate Changes Across the Triassic-jurassic Transitionmentioning
confidence: 74%
“…The Upper Triassic Dictyophyllum-Clathropteris macroflora of the Xujiahe Formation is replaced by the Lower Jurassic Ptilophyllum-Coniopteris flora in the Zhenzhuchong Formation (Ye et al, 1986), and the Upper Triassic Dictyophyllidites-Kyrtomisporis-Ovalipollis-Ricciisporites palynological assemblage is replaced by the Lower Jurassic Dictyophyllidites-Classopollis-Cycadopites assemblage (Lu and Wang, 1987;Wang et al, 2010). Previous palynological and macrofloral studies dated the Xujiahe Formation as Norian to Rhaetian in age (Ye et al, 1986;Lu and Wang, 1987;Wang et al, 2010;Li et al, 2016Li et al, , 2018. The Sulcocythere-Oncocythere-Darwinulla ostracod assemblage and the Burmesia-Myophora (Costatoria) Yunnanophorus-Pemophorus-Weiyuanella bivalve assemblages of the Xujiahe Formation also indicate a Norian to Rhaetian age (Wei, 1982;Gou, 1998;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Traditionally, four major basins have been the focus of Chinese Triassic palaeobotany, all with well-exposed continental Triassic successions yielding diverse macro-and microfloras. These basins are the Junggar and Tarim basins in the northwestern part of the country (Deng et al, 2010;Sha et al, 2011Sha et al, , 2015Peng et al, 2018a), the Ordos Basin in North China (Qu, 1980;Huang and Zhou, 1980) and the Sichuan Basin in South China (Wang et al, 2010;Li et al, 2016aLi et al, , 2016bLi et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%